The forestry question considered historically - Falkiner, C. Litton (Statistical and Social Inquiry Society of Ireland, 1906)
The main object of this paper is not to re-state the case for forestry in Ireland, but to recall public attention to the subject; and in doing so to endeavour to throw light on the solution of a preliminary difficulty which is encountered on the threshold of any attempt to extend our woodlands, viz. :?Where should planting" begin, and what are the districts in which it may be most hopefully undertaken? It appears to me that the past may have some lessons for us on this point, and that something may be done from the point of view of history to supply an answer to this question. The line of my recent reading chancing to have brought vividly before me the extent and value of our former forests, I have asked myself whether light may not be derived from a consideration of the localities in which those forests flourished, of the circumstances which caused their destruction, and of the attempts which have been made in former generations to repair or mitigate the misfortune of their disappearance? It is to these questions, and to these questions only, that I shall endeavour now to give an answer.
Read Friday, January 23rd, 1903
Keywords: Deforestation, Ireland; Woodlands, Ireland; Forests and Forestry, Ireland; 314.15